2022
DOI: 10.7759/cureus.27656
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Inflammatory Bowel Disease in Hospitalized Patients With Generalized Anxiety Disorder

Abstract: BackgroundThe development of inflammatory bowel disease (IBD), which encompasses ulcerative colitis and Crohn's disease, is multifactorial. Stress from anxiety is a risk factor for IBD. Generalized anxiety disorder (GAD) is twice as likely in IBD patients. This study explores the outcomes of patients hospitalized for IBD with comorbid GAD. MethodsA retrospective analysis utilizing the 2014 USA National Inpatient Sample database was performed to assess the outcomes of hospitalized IBD patients with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…The study with the largest sample reported the greatest prevalence of depressive disorders in female inpatients (68%) [ 32 ]. Similar data were reported for anxiety disorders [ 32 , 34 ]. Taken as a whole, the different authors agree that patients with IBD have a higher probability to develop affective disorders compared with the general population and that female gender represents a risk factor.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The study with the largest sample reported the greatest prevalence of depressive disorders in female inpatients (68%) [ 32 ]. Similar data were reported for anxiety disorders [ 32 , 34 ]. Taken as a whole, the different authors agree that patients with IBD have a higher probability to develop affective disorders compared with the general population and that female gender represents a risk factor.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the included studies had a retrospective design [ 29 , 30 , 31 , 32 , 33 , 34 ], three were cross-sectional [ 35 , 36 , 37 ], and three were prospective [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations